2012
DOI: 10.1021/ol300200m
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Catalyzed Synthesis of Aspergillide B: An Alkyne Addition Strategy

Abstract: A catalytic enantioselective formal total synthesis of aspergillide B is reported. This linchpin synthesis was enabled by the development of new conditions for Zn-ProPhenol catalyzed asymmetric alkyne addition. This reaction was used in conjunction with ruthenium-catalyzed trans-hydrosilylation to affect the rapid construction of a late-stage synthetic intermediate of aspergillide B to complete a formal synthesis of aspergillide B in a highly efficient manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 43 publications
2
17
0
3
Order By: Relevance
“…[43] Substrate and reaction optimization enabled alkynylation using just 1 equivalent of the precious alkyne 22 (see Table 8). Subsequent Ru-catalyzed hydrosilylation was used to achieve an E -selective reduction while also differentiating the two alkenes present in the product and enabling selective hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…[43] Substrate and reaction optimization enabled alkynylation using just 1 equivalent of the precious alkyne 22 (see Table 8). Subsequent Ru-catalyzed hydrosilylation was used to achieve an E -selective reduction while also differentiating the two alkenes present in the product and enabling selective hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Trost et al. reported the formal synthesis of aspergillide B 81 (Scheme b) . This concise asymmetric route features two separate alkynylation steps to generate intermediate 80 , which was converted to the natural product in 6 steps …”
Section: Catalytic Asymmetric Addition To Carbonylsmentioning
confidence: 99%
“…In 2012, Trost et al reported the formal synthesis of aspergillide B 81 (Scheme 20 b). [43] This concise asymmetric route features two separate alkynylation steps to generate intermediate 80, which was converted to the natural product in 6 steps. [44] The asymmetric alkynylation of aromatic and a,b-unsaturated aldehydes was utilized in the total synthesis of Acetaldehyde 89 is a challenging electrophile in asymmetric additions due to its propensity to undergo self-aldol processes.…”
Section: Asymmetric Alkyne Additionmentioning
confidence: 99%
“…Im Jahr 2012 berichteten Trost et al. über die Synthese von Aspergillid B 81 (Schema b) . Dieser kurze asymmetrische Weg beinhaltete zwei separate Alkinylierungsschritte zum Intermediat 80 , das dann in nur 6 Schritten in den Naturstoff 81 überführt wurde …”
Section: Katalytische Asymmetrische Addition An Carbonyleunclassified
“…[41] Das Schlüsselintermediat 69 wurde mit 84 % ee erhalten und durch eine Die Zn-ProPhenol-katalysierte asymmetrische Alkinylierung wurde gleichfalls bei der Totalsynthese von (À)-Adociacetylen B 75 eingesetzt (Schema 20 a). [ [43] Dieser kurze asymmetrische Weg beinhaltete zwei separate Alkinylie-rungsschritte zum Intermediat 80, das dann in nur 6 Schritten in den Naturstoff 81 überführt wurde. [44] Die asymmetrische Alkinylierung aromatischer und a,bungesättigter Aldehyde wurde bei der Totalsynthese von (+)-Spirolaxinmethylether 88 eingesetzt (Schema 21).…”
Section: Asymmetrische Alkin-additionunclassified